DESIGN AUDIT: VISUAL IDENTITY OF HET HUISJE CAFE - Gredi Gradana Sembada; Chandra Renaldi (KalaTanda, 2016)
The cafe business continues to experience significant developments, cafes being a favorite location to gather as part of the community's lifestyle. Currently there are more than ten thousand cafes in all corners of the country. In the 2013-2018 edition, the total revenue of the cafe sector is predicted to increase from USD 3.4 billion to USD 4.16 billion.The lifestyles of urban societies socializing in cafes are made a profit-making opportunity for business people by creating cafes with unique concepts. One of them is Het Huisje cafe. The cafe, which was established in early 2016, is located on Jl. Arif Rahman Hakim no. 9A, Pancoran Mas, Depok. the profit earned by Het Huisje cafe is static, in one month only a 10% increase in profit. Branding activities took the role of the case. The Het Huisje cafe logo that is not yet strongly illustrates the concept of its business. Visual Audit Results from pre-research Designs Audit, Het Huisje cafe logos do not meet the criteria of a good logo. The first phase of the study focused on visual audit on the logo. Methods of data collection using field observation instruments, interviews and questionnaires. Analysis using Design Audit matrix.The results of analysis in addition to being input for the design of promotional strategies are also used as input for the preparation of the design strategy process. The benefits of this research can be considered in making business decisions related to the field of design, so that the resulting design output is judged not only aesthetically, but also can be seen as a strategic step in achieving business goals